Penerapan Akad Musyarakah dan Musyarakah Mutanaqisah dalam Pembiayaan Proyek Jalan Tol: Studi Analisis Implementasi dan Tantangan di Indonesia - Abdul Fattah; Oyo Sunaryo Mukhlas (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research examines the implementation of musyarakah and musyarakah mutanaqisah contracts in financing toll road infrastructure in Indonesia. The significant funding required for toll road development presents an opportunity for Islamic banking to contribute through partnership-based financing instruments. This study analyzes financing structures, compliance with Sharia principles, risk allocation, and implementation challenges through real cases in Indonesia, such as the Trans-Java Toll Road, the Serpong-Balaraja Toll Road, and the Cileunyi-Sumedang-Dawuan (Cisumdawu) Toll Road. This research uses a descriptive qualitative approach with content analysis of legal documents and financial reports. The results show that innovative Sharia financing structures can overcome the limitations of conventional investment, but are still faced with challenges in regulation, contract standardization, and the capacity of Islamic financial institutions in financing large-scale project.